Tuvalu : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
Tuvalu is one of the smallest and most isolated countries in the world. With a population of some 11,000 people living on 26 square kilometers, Tuvalu is more than 3,000 kilometers away from its nearest major external market (New Zealand). The country faces tremendous challenges stemming from its remoteness, lack of scale economies, weak institutional capacity, and, above all, climate change and rising sea levels, which threaten the country's very existence. (Appendix III).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet